Enhanced selectivity in mixed matrix membranes for CO2 capture through efficient dispersion of amine-functionalized MOF nanoparticles - Ghalei,B; Sakurai,K; Kinoshita,Y; Wakimoto,K; Pournaghshband,Isfahani A; Song,Q; Doitomi,K; Furukawa,S; Hirao,H; Kusuda,H; Kitagawa,S; Sivaniah,E (Nature Energy, 2017)
Mixed matrix membranes (MMMs) for gas separation applications have enhanced selectivity when compared with the pure polymer matrix, but are commonly reported with low intrinsic permeability, which has major cost implications for implementation of membrane technologies in large-scale carbon capture projects. High-permeability polymers rarely generate sufficient selectivity for energy-efficient CO2 capture. Here we report substantial selectivity enhancements within high-permeability polymers as a result of the efficient dispersion of amine-functionalized, nanosized metal–organic framework (MOF) additives. The enhancement effects under optimal mixing conditions occur with minimal loss in overall permeability. Nanosizing of the MOF enhances its dispersion within the polymer matrix to minimize non-selective microvoid formation around the particles. Amination of such MOFs increases their interaction with thepolymer matrix, resulting in a measured rigidification and enhanced selectivity of the overall composite. The optimal MOF MMM performance was verified in three different polymer systems, and also over pressure and temperature ranges suitable for carbon capture.